Mulher, trabalho e família: a inserção feminina no mercado de trabalho da região metropolitana de São Paulo (1989 2008) - Jorge, Simone Aparecida (2009)
The main objective of this thesis was focused in the study and analysis of transformations that were originated by the woman participation in the workforce and consequently, the changes in her role in the family. We tried to identify these transformations and point to the new configurations in the Metropolitan Region of São Paulo MRSP, in the period 1989 to 2008. The thesis was based in the theoretical approaches and in the analysis of the base of datas recently elaborated by SEADE Fundação Sistema Estadual de Análise de Dados (State System Foundation to Datas Analysis) and DIEESE Departamento Intersindical de Estatística e Estudos Socioeconômicos (Department for Inter trade union Statistic and Socioeconomic Studies). Simultaneously, we promoted comparative analysis of these datas with National researches, like the PNAD Pesquisa Nacional por Amostra de Domicílios (National Research through Residence Samples) elaborated by IBGE Instituto Brasileiro de Geografia e Estatística (Brazilian Institute of Geography and Statistic). The research elected as main hypothesis the assertive that, in spite of new family shapes and transformations in the female participation in the MRSP workforce in the studied period, the inequality between the genders still remains with effects in the sociability between women and men